The Dynamics of Constitutional Law and The Challenges of Democratic Practices in Indonesia - Latif, Abdul; Ikram, Muhammad Dzul; Putra, Marta Satria (Advances In Social Humanities Research, 2025)
The development of constitutional law in Indonesia has significantly transformed since the 1998 reform, especially through amendments to the 1945 Constitution aimed at strengthening democracy, the rule of law, and government transparency. However, challenges persist in fully realizing democratic principles and good governance, including political oligarchy, biased election organizers, weak checks and balances between state institutions, money politics, and the high presidential threshold, which hinder fair political competition. This research aims to analyze the dynamics of constitutional law in Indonesia, identify challenges in the practice of democracy, and formulate the reconstruction of an ideal constitutional legal system to strengthen the rule of law and substantive justice. Using the normative juridical and empirical approaches, this research examines the applicable regulations and compares them with the constitutional system in several other countries. The results show that reforming the electoral system, strengthening the independence of the EMB, and increasing the effectiveness of law enforcement are the main steps needed to improve the constitutional law system in Indonesia. As a solution, this study recommends the reconstruction of constitutional law regulations that are more responsive to the challenges of the times by emphasizing the strengthening of the supremacy of the constitution, improving the electoral system, and increasing transparency and accountability in government. The novelty of this research lies in analyzing the weaknesses of the post-reform constitutional legal system and strategic proposals to build a more substantial and equitable democracy. With a more comprehensive legal reform, Indonesia is expected to build a more inclusive, accountable, and democratic system based on the rule of law.